2004
DOI: 10.1890/03-3146
|View full text |Cite
|
Sign up to set email alerts
|

Invading Herbivory: The Golden Apple Snail Alters Ecosystem Functioning in Asian Wetlands

Abstract: Abstract. We investigated the effects of an exotic snail, the golden apple snail (Pomacea canaliculata) on biodiversity and ecosystem functioning in tropical wetland ecosystems. This large snail (up to 80-mm shell height) has invaded large parts of Southeast Asia during recent decades. A survey of natural wetlands in Thailand showed that high densities of the snail were associated with almost complete absence of aquatic plants, high nutrient concentrations, and high phytoplankton biomass, that is, a complete s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
267
3
7

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 343 publications
(286 citation statements)
references
References 30 publications
9
267
3
7
Order By: Relevance
“…Other study also showed that when different food types were offered, P. canaliculata grazed heavily on both species of macrophytes provided 10 . A study conducted in Laos also supported this study that the absence of aquatic plants in wetlands may be linked to the presence of P. canaliculata as this species can eat almost any plant 15 . In contrast, P. scutata tended to be selective for food as it preferred S. cucullata over other species.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Other study also showed that when different food types were offered, P. canaliculata grazed heavily on both species of macrophytes provided 10 . A study conducted in Laos also supported this study that the absence of aquatic plants in wetlands may be linked to the presence of P. canaliculata as this species can eat almost any plant 15 . In contrast, P. scutata tended to be selective for food as it preferred S. cucullata over other species.…”
Section: Discussionsupporting
confidence: 71%
“…Our study is in agreement with that of Carlsson 15 who reported that P. canaliculata had a strong negative effect on the growth and biomass of the preferred plants S. cucullata and L. adscendens that had been grazed down to very low levels. According to local residents, S. cucullata and L. adscendens have disappeared from the Vientiane wetlands since the snail was introduced in 1992 15 . Substantial grazing by P. scutata on S. cucullata may likely have been due to the softness of this plant species or perhaps it was easier to eat since it is a floating type of vegetation.…”
Section: Discussionmentioning
confidence: 99%
“…Although this may have played a role in the present study, the Wolffia outbreak is more likely to have resulted from the complete elimination of apple snails (Ampullariidae; Table 4). Apple snails are known to be efficient grazers of aquatic macrophytes and have even been reported to leave the water column to forage for plants (Carlsson et al 2004;Dudgeon 1999). The complete coverage of the water surface by Wolffia sp.…”
Section: Effects On Other End Points and Ecologic Effect Chainmentioning
confidence: 99%
“…Biotic interactions are major drivers for ecosystem functioning and evolutionary processes, being capable of altering ecosystem productivity [1], determining geographical distributions of species [2] and influencing evolutionary processes. In the present context of global environmental crisis, understanding the dynamic interplay between climate and species interactions is crucial to predict how ecosystems will respond to climate change.…”
Section: Introductionmentioning
confidence: 99%